2017
DOI: 10.1016/j.ekir.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Daily Activity Levels and Estimated Kidney Function in Men and Women With Predialysis Chronic Kidney Disease

Abstract: IntroductionChronic kidney disease (CKD) is often accompanied by complications including poor physical activity level. However, only a few studies have objectively characterized physical activity levels in predialysis CKD. Our study sought to measure daily activity levels by accelerometry in individuals with CKD (stages III−V) and to determine the association between daily activity and kidney function.MethodsWe determined kidney function by means of the estimated glomerular filtration rate (eGFR) using the Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It was recently reported that a standard group of stage 3–5 nondialysis CKD patients acquired only 6 ± 9 min of moderate‐to‐vigorous intensity physical activity per day, suggesting that these patients achieve far less than the national recommendations of 150 min per week (West et al. ). Similarly, significantly reduced VO 2 peak measurements have been reported in patients with CKD when compared to sedentary age‐predicted norms (Padilla et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that a standard group of stage 3–5 nondialysis CKD patients acquired only 6 ± 9 min of moderate‐to‐vigorous intensity physical activity per day, suggesting that these patients achieve far less than the national recommendations of 150 min per week (West et al. ). Similarly, significantly reduced VO 2 peak measurements have been reported in patients with CKD when compared to sedentary age‐predicted norms (Padilla et al.…”
Section: Discussionmentioning
confidence: 99%
“…The medication-specific risk factors were angiotensin-converting-enzyme inhibitors (ACEIs) 63–66 , angiotensin II receptor blockers (ARBs) 63–67 , metformin 68 , statins 69 , non-steroidal anti-inflammatory drugs (NSAIDs) 50,63–66,70,71 , proton pump inhibitors (PPIs) 64,65,7274 , and allopurinol 63,65,75 . Finally, the lifestyle-related risk factors were smoking 38,39,4143,50,59,7679 , alcohol consumption 41,43,76,80,81 , and physical activity 43,59,8285 .…”
Section: Methodsmentioning
confidence: 99%
“…However, based on the 12-Item Short Form Health Survey (SF-12) questionnaire, Barthel Index, and Timed Up-And-Go Test, they found no differences in the HRQoL of these patients. In addition, a Canadian study showed that there was no relationship between physical activity levels (measured using pedometers) and renal function (assessed by glomerular filtration rates), although the authors did note that patients with CKD-5D had a sedentary lifestyle (West et al, 2017). A similar study in Spain concluded that there were no differences in physical activity levels or HRQoL in patients with CKD-5D, although this cohort excluded patients aged over 70 years and only included six patients on HD and eight patients on PD (Hernández Sánchez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%